Bild unserer irren Anwesenheit/auf der Oberfläche der Erde. L’immagine come storia naturale del presente nella poetica diW. G. Sebald - Tedesco, Salvatore (Bollettino Filosofico, 2017)
The poem Nach der Natur by W. G. Sebald, real germinal place of its author’s subsequent literary production, is a salient moment of confrontation for today's philosophical gaze; our historical time and our own humanity are configured as “natural history” (Benjamin), in a compositional game in which the present time acquires the character of a timeless distance projecting it on the background of a mournful nature, entrusting to the roughness of the poetic material and to its conceptual weaving the task of an unprecedented presentification of some layers of reality of rare density.